Sulfated TiO2 nanosheets catalyzing conversion of biomass derivatives: influences of the sulfation on distribution of Brønsted and Lewis acidic sites. Issue 5 (11th January 2020) - Shao, Yuewen; Du, Wenfei; Gao, Zhiran; Sun, Kai; Zhang, Zhanming; Li, Qingyin; Zhang, Lijun; Zhang, Shu; Liu, Qing; Hu, Xun
Abstract: BACKGROUND: The synthesis of solid acid catalysts of recoverable and environmentally friendly nature has gained increasing attention in recent years. The distribution of Brønsted and Lewis acidic sites on the surface of sulfated metal oxides determines the catalytic performance, which is affected by many key factors, such as the concentration of sulfuric acid impregnated and the morphology of the metal oxides used. In this study, TiO2 nanosheets were successfully synthesized and used as carrier for the preparation of solid acid catalysts. RESULTS: The concentration of sulfuric acid for the impregnation resulted in various distributions of Brønsted and Lewis acidic sites on the surface of sulfated TiO2 . With a medium concentration of sulfuric acid (1 mol L −1 ) for the impregnation, the highest ratio of Brønsted to Lewis acidic sites can be achieved, and the catalyst showed superior catalytic activity for the conversion of furfuryl alcohol (FA) to ethyl levulinate (EL) in ethanol and the conversion of fructose to 5‐hydroxymethylfurfural (HMF) in dimethyl sulfoxide (DMSO). CONCLUSION: The sulfation of TiO2 nanosheets induced the formation of both Brønsted and Lewis acidic sites. The Brønsted acidic sites were more effective for catalyzing the conversion of FA or fructose. The poor recyclability of the 1.0‐SO4 2− /TiO2 catalyst in the conversion of FA to EL in ethanol, a protic solvent, was due to the leaching of sulfur species. The deactivation of the catalyst in DMSO was due to coking, which could be resolved via calcination of the coke species in air. © 2019 Society of Chemical Industry